2015
DOI: 10.1002/2015ms000474
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vertical wind shear on the predictability of tropical cyclones: Practical versus intrinsic limit

Abstract: The effects of environmental shear on the dynamics and predictability of tropical cyclones (TCs) are further explored through a series of cloud-permitting ensemble sensitivity experiments with small, random initial condition perturbations on the low-level moisture fields. As an expansion of earlier studies, it is found that larger the shear magnitude, less predictable the TCs, especially the onset time of the rapid intensification (RI), until the shear is too large for the TC formation. Systematic differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 40 publications
3
48
0
Order By: Relevance
“…(We did not examine the effects of initial structural error, as the specification of the radius of maximum wind is effectively the only free structural parameter in CHIPS, but this source of error may be important in real storms.) The high sensitivity to initial intensity error when the initial intensity is small may be owing to the striking sensitivity of the timing of rapid intensification of weak storms to shear documented by Zhang and Tao (2013) and Tao and Zhang (2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(We did not examine the effects of initial structural error, as the specification of the radius of maximum wind is effectively the only free structural parameter in CHIPS, but this source of error may be important in real storms.) The high sensitivity to initial intensity error when the initial intensity is small may be owing to the striking sensitivity of the timing of rapid intensification of weak storms to shear documented by Zhang and Tao (2013) and Tao and Zhang (2015).…”
Section: Discussionmentioning
confidence: 99%
“…We interpret this as stemming from the greater potential for rapid intensification of initially weak storms compared to storms that are already not far from their potential intensities and to the great sensitivity of the timing of rapid intensification to shear when the initial intensity is small (Zhang and Tao 2013;Tao and Zhang 2015). This suggests that future work might focus on predictability of rapidly intensifying events and/or on events that achieve major hurricane intensity.…”
Section: Error Growth In a Tropical Cyclone Risk Assessment Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have shown an interrelation between the variation of GW momentum fluxes in the LS and the intensity of zonal wind (Sato & Dunkerton, ; Vincent & Joan Alexander, ). GW energy is reduced in the presence of strong vertical wind shear (Tao & Zhang, ; Tsuda, ; Zhang & Tao, ). In the present study, the seasonal pattern indicates that the lowest zonal and meridional wind shears correspond to the maximum GW energy in the LS in monsoon months.…”
Section: Discussionmentioning
confidence: 99%
“…To account for the differences in the behavior of multiscale processes, researchers have previously used ensemble simulations of perturbed initial conditions to achieve an improved forecast as compared to individual deterministic forecasts (Berner et al, 2011;Finocchio & Majumdar, 2017;Tao & Zhang, 2015;Zhang & Tao, 2013). did a Fourier decomposition of the flow field within the vortex and investigated the error growth of individual wave numbers (WNs) within TCs while imposing stochastic perturbations at various scales internal as well as external to the TC vortex.…”
Section: Strides Made Thus Farmentioning
confidence: 99%